(untitled) (Kronika Bydgoska, 2016)
In the building of the Classical Grammar School in Wolności Square in Bydgoszcz, erected in the second half of the 1870’s, a collection of ”teaching aids” was gathered successively. Among others, the school interiors were decorated with reproductions of ancient sculptures (e.g. Laokoon group, Apollo Belvedere, Diana - the Huntress), reproductions of a series of 16 paintings depicting the Odyssey by Frederick Preller Sr. (1804-1878), and engravings by Domenico de Rossi with views of baroque Rome. Besides their didactic tasks, they were a reflection of the partitioner’s political and philosophical trends in those days. The German authorities were very involved in the archaeological excavations organised in the 19th century, and Germany being united considered itself the inheritor of antiquity. Future citizens educated in the elite institution of Bydgoszcz had every day a chance to commune with the beauty being part of a well thought-out propaganda program.